Issues in making courseware exploitable - Douglas Siviter; Phil Siviter (Association for Learning Technology, 1995)
There are currently substantial investments being made in courseware development in the UK, in particular in the HÈFCs' Teaching and Learning Technology Programme (TLTP), and the hope which underpins these development efforts is that Higher Education institutions will eagerly adopt and exploit the freely available courseware which emerges from them. Unfortunately, there are many reasons why this is probably going to be an over-optimistic assumption (Laurillard et al, 1993). The bottlenecks which can impair the successful exploitation of courseware range from cultural to technical, and are quite diverse. In this paper we discuss some of these bottleneck issues and suggest approaches to dealing with them. We deliberately restrict our discussion to technical bottlenecks, and therefore discuss issues of courseware design, courseware development, and courseware management.